A randomised comparison of resuscitation with an anaesthetic rebreathing circuit or an infant ventilator in very preterm infants. Issue 6 (21st October 2004) - Menakaya, J; Andersen, C; Chirla, D; Wolfe, R; Watkins, A
Abstract : Twenty four preterm infants (< 27 weeks gestation) were randomised to resuscitation with an anaesthetic rebreathing circuit or a ventilator with volume guarantee. There was no difference in weight or gestation between the groups. End expiratory pressures were higher and less variable with the ventilator. This pilot study shows that very preterm infants can be safely and effectively resuscitated using a ventilator.